ALTERATION ON THE CHEMICAL COMPOSITION OF THE SOLID AND LIQUID PHASES OF AN ACID SOIL BY LIME AND GYPSUM APPLICATION - Oliveira, Hatila Julião de; Ernani, Paulo Roberto; Amarante, Cassandro Vidal Talamini do (Revista de Ciências Agroveterinárias, 2002)
Soil Ca availability depends on both the concentration of Ca in the soil solution and the capability of the solid phase to keep Ca activity unaffected as plant uptake takes place, and these parameters are affected by the Ca source. This study was carried out to quantify the effect of lime or gypsum application on soil parameters related to acidity with emphasis on Ca. Rates of dolomitic lime (0, 3, 6, 9, 12 and 18 Mg ha-1) or agricultural gypsum (0, 3, 6 9 and 12 Mg ha-1) were applied to samples of a very acid soil (Haplumbrept) then incubated for three months at room temperature. After incubation, some Chemical determinations were performed in the solid and liquid phases, and the selectivity coefficients between cations were calculated. Lime increased pH and the exchangeable and soluble values of Ca and Mg, decreased Al in both phases and the soluble K. Addition of gypsum had no effect on soil pH, but increased the exchangeable Ca and the concentration of Ca, Mg, Al and K in the liquid phase. Gypsum was the product that most increased solution Ca despite having lower content of Ca than lime. Thus, gypsum can be a good choice for Ca supplying where high values of Ca in solution are needed or when is required a rapid downward movement of Ca in the profile. Cation preference for the negative charges in the limed soil followed the order: Al > Ca > Mg > K; in the samples that received gypsum, the preference varied with the rate applied and for some cations the behavior was opposite of that verified on limed samples.